BOOM BHOI: FUNCTIONAL FOOD INNOVATION BASED ON SESAME (Sesamum Indicum L.) THROUGH THE TRANSFORMATION OF BHOI (Traditional Acehnese Cake) AS AN EFFORTS TO PREVENT STUNTING IN NORTH ACEH DISTRICT - Izwanda, Zainur (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Stunting remains a major public health problem in Indonesia, including North Aceh Regency, affecting children's physical growth, cognitive development, and future productivity. Efforts to reduce stunting require sustainable nutritional interventions that utilize locally available resources. Sesame (Sesamum indicum L.) is rich in protein, calcium, iron, zinc, healthy fats, and antioxidants, making it a promising ingredient for functional food development. Therefore, BOOM BHOI was developed by incorporating sesame into bhoi, a traditional Acehnese cake, to enhance its nutritional value while preserving local culinary heritage. Objective: To develop BOOM BHOI as a sesame-based functional food innovation that can serve as a nutritious snack alternative and support stunting prevention efforts in North Aceh Regency. Methods: This innovation was developed through problem identification related to stunting, product formulation by incorporating sesame into traditional bhoi recipes, product processing, and evaluation of nutritional characteristics and consumer acceptability. The approach integrated local resource utilization, food innovation, and the preservation of Acehnese traditional cuisine. Results: BOOM BHOI was successfully developed as a functional food product with improved nutritional value compared to conventional bhoi. The addition of sesame increased the content of protein, essential minerals, and antioxidants without significantly altering the taste, texture, and sensory characteristics preferred by consumers. The product has potential as a healthy snack for children, pregnant women, and breastfeeding mothers, while also creating opportunities for community-based entrepreneurship and local economic development. Conclusion: BOOM BHOI represents an innovative functional food based on local wisdom that has the potential to contribute to stunting prevention through the provision of nutrient-rich food. By utilizing locally available ingredients and a culturally accepted traditional product, BOOM BHOI not only supports nutritional improvement but also promotes the preservation of Acehnese culinary heritage and community economic empowerment in North Aceh Regency.